Biomimetic electrospun scaffolds for engineered heart tissue: from design parameters to drug testing platforms - Vaiciuleviciute, Raminta; Alaburda, Aidas; Uzieliene, Ilona; Kistamás, Kornél; Lengyel, Máté; Dinnyés, András; Bergaud, Christian; Bernotiene, Eiva (Frontiers in Bioengineering and Biotechnology, 2026)
Electrospun nanofibers have emerged as a promising platform for cardiac tissue engineering, offering unique opportunities to recapitulate the native myocardial extracellular matrix (ECM) architecture. This comprehensive review examines the critical design parameters affecting cardiomyocyte function and maturation on electrospun scaffolds, including fiber diameter, material composition, alignment, and pore architecture. Recent advances in conductive polymers and hybrid material systems have shown particular promise for enhancing electrical coupling and functional maturation of stem cell-derived cardiomyocytes. However, significant challenges remain in achieving complete cardiomyocyte maturation, particularly regarding calcium handling properties and metabolic characteristics. This review synthesizes current knowledge on technical characteristics of biomimetic nanofibrous scaffolds, identifying future directions for translating these approaches toward realistic cardiac models and potential clinical cardiac regenerative applications.